Electrodiagnostic assessment of the autonomic nervous system: A consensus statement endorsed by the American Autonomic Society, American Academy of Neurology, and the International Federation of Clinical Neurophysiology. Issue 2 (February 2021) - Cheshire, William P.; Freeman, Roy; Gibbons, Christopher H.; Cortelli, Pietro; Wenning, Gregor K.; Hilz, Max J.; Spies, Judith M.; Lipp, Axel; Sandroni, Paola; Wada, Naoki; Mano, Akiko; Ah Kim, Hyun; et al.
Highlights: Sensitive, validated, noninvasive electrodiagnostic tests of autonomic function have been developed. An international expert panel provides evidence-based recommendations to guide autonomic testing. Recommendations allow for standardized assessment of severity and distribution of autonomic failure. Abstract: Evaluation of disorders of the autonomic nervous system is both an art and a science, calling upon the physician's most astute clinical skills as well as knowledge of autonomic neurology and physiology. Over the last three decades, the development of noninvasive clinical tests that assess the function of autonomic nerves, the validation and standardization of these tests, and the growth of a large body of literature characterizing test results in patients with autonomic disorders have equipped clinical practice further with a valuable set of objective tools to assist diagnosis and prognosis. This review, based on current evidence, outlines an international expert consensus set of recommendations to guide clinical electrodiagnostic autonomic testing. Grading and localization of autonomic deficits incorporates scores from sympathetic cardiovascular adrenergic, parasympathetic cardiovagal, and sudomotor testing, as no single test alone is sufficient to diagnose the degree or distribution of autonomic failure. The composite autonomic severity score (CASS) is a useful score of autonomic failure that is normalized for age and gender. Valid indications for autonomic testing include generalized autonomic failure, regional or selective system syndromes of autonomic impairment, peripheral autonomic neuropathy and ganglionopathy, small fiber neuropathy, orthostatic hypotension, orthostatic intolerance, syncope, neurodegenerative disorders, autonomic hyperactivity, and anhidrosis.